2022
DOI: 10.1111/jocd.14795
|View full text |Cite
|
Sign up to set email alerts
|

Depth profiling of epidermal hydration inducing improvement of skin roughness and elasticity: in vivo study by confocal Raman spectroscopy

Abstract: Introduction Skin hydration in the stratum corneum plays an important role in skin condition, and skin efficacy properties are influenced by its hydration level. However, few studies have identified the correlation between changes in skin hydration content and skin characteristics by skin depth level. Aims This study aims to determine how changes in skin hydration at specific depth levels affect skin condition by long‐term tracking changes in hydration of stratum corneum and viable epidermis after usage of moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…It is well known that skin hydration in the stratum corneum plays a crucial role in skin condition and, vice versa, that its hydration level influences the skin's efficacy properties. However, few studies have been performed to establish a correlation between modifications in skin hydration content and skin characteristics at different skin depth [33]. For example, the skin hydration measured by the dermoanalyser penetrates to a depth of 10-20 µm of the stratum corneum [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that skin hydration in the stratum corneum plays a crucial role in skin condition and, vice versa, that its hydration level influences the skin's efficacy properties. However, few studies have been performed to establish a correlation between modifications in skin hydration content and skin characteristics at different skin depth [33]. For example, the skin hydration measured by the dermoanalyser penetrates to a depth of 10-20 µm of the stratum corneum [28].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the skin hydration measured by the dermoanalyser penetrates to a depth of 10-20 µm of the stratum corneum [28]. It has been demonstrated that skin elasticity is influenced by its hydration level at viable epidermis depths, while skin roughness is more affected by hydration at the stratum corneum level [33]. This highlights the importance of determining the effect of topically applied formulations on hydration at the stratum corneum and of monitoring skin elasticity or the depth profile of water content using other techniques such as Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…When the facial skin around the pores is properly hydrated, the stratum corneum inside and surrounding the pores swells, and the size of the pores and their surface area are reduced accordingly [ 44 ]. Since skin elasticity is partly influenced by skin hydration levels at viable epidermis depths and skin roughness at the stratum corneum, it is conceivable that the GEN product may lead to enhanced skin elasticity as well [ 45 ]. However, the present study had no parameters representative of skin elasticity, so the benefit of the GEN product on this feature may require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A possible limitation of this study derives from the fact that specific measurements of skin elasticity, an important parameter for the analysis of skin rejuvenation, were not performed. However, given that skin hydration levels are strongly correlated with skin elasticity, 24 the improvement recorded in hydration levels can be considered an indirect index of the improvement in the degree of elasticity.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that skin hydration levels are strongly correlated with skin elasticity, 24 the improvement recorded in hydration levels can be considered an indirect index of the improvement in the degree of elasticity.…”
Section: Discussionmentioning
confidence: 99%